Graphitic Carbon Nitride Nanosheet-Carbon Nanotube Three-Dimensional Porous Composites as High-Performance Oxygen Evolution Electrocatalysts - Ma, Tian Yi; Dai, Sheng; Jaroniec, Mietek; Qiao, Shi Zhang (Angewandte Chemie International Edition, 2014)
A new class of highly efficient oxygen evolution catalysts has been synthesized through the self‐assembly of graphitic carbon nitride nanosheets and carbon nanotubes, driven by π–π stacking and electrostatic interactions. Remarkably, the catalysts exhibit higher catalytic oxygen evolution activity and stronger durability than Ir‐based noble‐metal catalysts and display the best performance among the reported nonmetal catalysts. This good result is attributed to the high nitrogen content and the efficient mass and charge transfer in the porous three‐dimensional nanostructure. Combining C and N to make O: 3D porous graphitic carbon nitride nanosheet–carbon nanotube composites have been synthesized through a spontaneous assembly process. The high nitrogen content, enhanced electron conductivity, and improved mass transport result in excellent catalytic oxygen evolution activity and strong durability, superior to those reported for other nonmetal catalysts and noble‐metal catalysts (see figure; OER: oxygen evolution reaction).